Investigating SMYD3 role during oocyte maturation in a 3D follicle-enclosed oocyte in vitro model in sheep - Camerano Spelta Rapini, Chiara; Peserico, Alessia; Di Berardino, Chiara; Capacchietti, Giulia; Rojo-Fleming, Camila; Damian-Buda, Andrada-Ioana; Unalan, Irem; Boccaccini, Aldo Roberto; Grossi, Valentina; Mattioli, Mauro; Barboni, Barbara (Frontiers in Cell and Developmental Biology, 2025)
BackgroundSMYD3 is a histone methyltransferase known for its dual role in modifying both histone and non-histone proteins. Despite its established involvement in somatic cell function and oncogenesis, its role in mammalian oogenesis and early embryonic development remains unclear. This study aimed to elucidate the function of SMYD3 in regulating oocyte meiotic progression and developmental competence using sheep as a mono-ovulatory model.ResultsUtilizing a 3D follicle-enclosed in vitro maturation (FEO-IVM) system, the study examined the impact of SMYD3 inhibition on oocyte maturation within Early Antral follicles In the absence of human chorionic gonadotropin oocytes remained arrested at the germinal vesicle (GV) stage. Interestingly, treatment with a SMYD3 inhibitor (iSMYD3) alone prompted germinal vesicle breakdown (GVBD) in 67% of oocytes; however, progression to the metaphase II (MII) stage was achieved only when iSMYD3 was combined with hCG, resulting in a 73% maturation rate. Despite this, MII oocytes from the iSMYD3 group exhibited compromised developmental competence, as evidenced by the failure of parthenogenetic embryos to progress beyond the 8-cell stage, contrasting with a 29% success rate in the hCG-only group. At the molecular level, SMYD3 inhibition led to sustained activation of CDC25A within oocytes, facilitating GVBD but impeding the MI-MII transition due to the absence of CDC25A degradation. Moreover, iSMYD3 failed to activate the MAPK1/3 and PDE5A pathways in the somatic compartment, unlike hCG treatment, indicating distinct signaling mechanisms. Additionally, hCG rapidly downregulated SMYD3 expression in follicular walls and cumulus cells, a process independent of meiotic progression but essential for metabolic decoupling between oocytes and cumulus cells. SMYD3 inhibition disrupted this decoupling by preventing hCG-induced gap junction closure, thereby maintaining prolonged intercellular communication.ConclusionSMYD3 is identified as a key modulator of oocyte maturation, orchestrating meiotic progression through CDC25A regulation and interacting with hCG-driven somatic signaling. These findings highlight SMYD3 as a critical determinant of late oogenesis and a potential target for enhancing oocyte competence in assisted reproductive technologies